THE CORRELATION BETWEEN STUDENTS’ READING SPEED AND THEIR READING COMPREHENSION ( A CORRELATION STUDY IN THE ELEVENTH GRADE OF SENIOR HIGH SCHOOL MAN 3 BANYUWANGI ) - Moh Dzikril Hakim, Dzikril (Faculty of Teaching and Education, University of August 17, 1945, Banyuwangi, 2021)
The Correlation Between Students’ Reading Speed And Their Reading Comprehension ( A Correlation Study In The Eleventh Grade Of Senior High School Man 3 Banyuwangi ). In this research, the researcher investigated wheter or not there was any significant correlation between reading speed and reading comprehension of the eleventh grade students of MAN 3 Banyuwangi in the 2020/2021 academic year. If there was any significant correlation between variables, the researcher wants to know how far the correlation was exiting between the variables. To answer the problem of the research, the researcher formulates the hypothesis which says that there is any significant correlation between reading comprehension achievement and writing skill of the elevent grade students of MAN 3 Banyuwangi in the 2020/2021 academic year. Furthermore, the researcher used proportional random sampling by slovin method to take the sample. Meanwhile, the respondents were the elevent grade students of MAN 3 Banyuwangi in the 2020/2021 academic year. To analyze main data, the Pearson Product Moment was used to prove whether or not there was any significant correlation between reading speed and reading comprehension. The result of the statistical calculation should be consulted to the critical value table product moment with the level of significance 5% with N=31. The critical value table is 0,355. Meanwhile, the value of statistical calculation was 0,744. It can be said that the null hypothesis was rejected and the alternative hypothesis was accepted since the r statistic (0,744) was proved to be higher than the critical value table (0,355), So, it can be concluded that there was any significant correlation between reading speed and reading comprehension of the eleventh grade students of MAN 3 Banyuwangi in the 2020/2021 academic year.